Pengaruh Servicescape terhadap Kepuasan Tamu Menginap di Fave Hotel Olo Padang - Putri, Audria Hani; Wulansari, Nidia (Lembaga Yasin AlSys, 2023)
This research was conducted due to guest dissatisfaction with the physical conditions at Favehotel Olo Padang. This research was conducted with the aim of assessing the extent to which the service environment at Favehotel Olo Padang affects the level of guest satisfaction. This study used a causal associative quantitative approach, in which the research sample consisted of 204 guests who had and are currently staying at Favehotel Olo Padang with an age of more than 17 years. Data analysis was performed using binary logistic regression method. The results showed that the servicescape variable had an effect of 10.9% on the level of guest satisfaction, while other variables not examined in this study had an effect of 89.1%. According to the hypothesis test, guest satisfaction at Fave Hotel Olo Padang is strongly influenced by the servicescape. The statistical test results showed that the null hypothesis (H0) was accepted and the alternative hypothesis (Ha) was rejected, with a chi-square table value of 7.814, a significance value of 0.452, and a chi-square value of 124.598.